2015
DOI: 10.1097/wnr.0000000000000348
|View full text |Cite
|
Sign up to set email alerts
|

Increasing breadth of semantic associations with left frontopolar direct current brain stimulation

Abstract: The aim of this study was to evaluate the influence of left frontopolar versus auditory (control) cortex transcranial direct current stimulation (tDCS) on the breadth of semantic associations produced in a cued free association task. A within-participants design administered anodal tDCS over the left frontopolar or auditory cortex, centered at electrode site AFZ or T7 using a 4×1 targeted stimulation montage. During stimulation, participants produced free associates in response to cues designed to promote narr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 28 publications
4
17
0
Order By: Relevance
“…With this greater focus on idea selection, potentiating left frontopolar cortex produced greater enhancements compared to the uncued—and less selective—conditions. Our study showed that, without a cue to think creatively, anodal tDCS to left frontopolar cortex was not associated with enhanced performance on the otherwise non-selective verb generation task (see also Brunye et al, 2015). Thus, only after emphasizing selectivity explicitly did potentiating left frontopolar cortex boost performance, suggesting support for the region’s contributions to creative idea selection.…”
Section: Creative Idea Selectionsupporting
confidence: 53%
“…With this greater focus on idea selection, potentiating left frontopolar cortex produced greater enhancements compared to the uncued—and less selective—conditions. Our study showed that, without a cue to think creatively, anodal tDCS to left frontopolar cortex was not associated with enhanced performance on the otherwise non-selective verb generation task (see also Brunye et al, 2015). Thus, only after emphasizing selectivity explicitly did potentiating left frontopolar cortex boost performance, suggesting support for the region’s contributions to creative idea selection.…”
Section: Creative Idea Selectionsupporting
confidence: 53%
“…Although the latter is speculative, future research may find value in examining whether neuromodulation of the left TPJ indeed carries implications for mental processes critical to real-world social functioning. The present findings also converge with a growing body of literature suggesting that individual differences may play an important moderating role in tDCS influences on cognitive function [22,24,25]. Indeed, tDCS may influence real-world cognitive processes in unexpected ways for individuals with varied knowledge, skills, and propensities.…”
Section: Resultssupporting
confidence: 87%
“…During tDCS sessions, as in our previous work [17,21,22], we asked participants to report perceived cutaneous sensation on a scale from 0 (Cold) to 9 (Hurts a Lot); ratings were requested immediately before tDCS onset, after reaching target intensity, after 10 min, and at the end of the session (after tDCS cessation). Ratings were collected to ensure similar perceived sensation across conditions and ensure participant comfort in accordance with human use approvals.…”
Section: Methodsmentioning
confidence: 99%
“…]. Rostromedial frontal clusters have been suggested to be part of the semantic memory network [Buckner et al, ] and might play a role in relational integration across semantic distance, as has been proposed by Green et al [] and Brunyé et al [].…”
Section: Discussionmentioning
confidence: 99%